Differential Dynamics of Extracellular and Cytoplasmic Domains in Denatured States of Rhodopsin - Dutta, Arpana (Biochemistry, 2014)
[Image: see text] Rhodopsin is a model system for understanding membrane protein folding. Recently, conditions that allow maximally denaturing rhodopsin without causing aggregation have been determined, opening the door to the first structural characterization of denatured states of rhodopsin by nuclear magnetic resonance (NMR) and electron paramagnetic resonance (EPR) spectroscopy. One-dimensional (1)H NMR spectra confirm a progressive increase in flexibility of resonances in rhodopsin with increasing denaturant concentrations. Two-dimensional (1)H–(15)N HSQC spectra of [(15)N]-α-lysine-labeled rhodopsin in which signals arise primarily from residues in the cytoplasmic (CP) domain and of [(15)N]-α,ε-tryptophan-labeled rhodopsin in which signals arise only from transmembrane (TM) and extracellular (EC) residues indicate qualitatively that EC and CP domains may be differentially affected by denaturation. To obtain residue-specific information, particular residues in EC and CP domains were investigated by site-directed spin labeling. EPR spectra of the spin-labeled samples indicate that the EC residues retain more rigidity in the denatured states than the CP residues. These results support the notion of residual structure in denatured states of rhodopsin.